Landasan Filsafat Antropologi-Teologis Dalam Pengembangan Kurikulum Pendidikan Kristen - Karnawati Karnawati; Priyantoro Widodo (Sekolah Tinggi Teologi Simpson, 2019)
Karnawati & Priyantoro Widodo, Anthropological-Theological Philosophy in the Development of the Christian Education Curriculum. The basis for developing a Christian education curriculum is guided by God as the